Report of a Case of Video-Assisted Thoracoscopic Resection of Bronchogenic Cyst Developed in the Aorto-Pulmonary Window. Issue 2 (1996) - De Giacomo, T.; Venuta, F.; Rendina, E. A.; Guarino, E.; Flaishman, I.; Ricci, C.
Abstract : We report the case of a 28-years-old male with a bronchogenic cyst developed in the aorto-pulmonary window. Left video-assisted thoracoscopy was performed and the cyst was removed intact and completely. Operative time was 48 minutes. The postoperative course was uneventful and the patient was discharged on the third postoperative day. We believe that an uncomplicated mediastinal bronchogenic cyst can be successfully approached by video-assisted thoracoscopy. In the case of an intraparenchymal or complicated cyst, thoracoscopic resection can be technically difficult and hazardous, and open approach is preferable.